Exploring Gen Z's Perspectives on English Learning in the Digital Era - Lubis, Rahma Fitri Yani; Siregar, Deasy Yunita (Institut Agama Islam Negeri Palopo, 2025)
This study explores how Gen Z perceives the role of Instagram in supporting their English learning in the digital era. As digital natives, Gen Z prefers interactive, visually engaging, and flexible learning experiences, making Instagram an appealing educational platform. This research employs a qualitative approach, utilizing semi-structured interviews and observations with 15 university students in North Sumatra who actively use Instagram for learning English. The findings reveal that Instagram facilitates enjoyable learning through its visual and interactive features, allowing students to improve their grammar, pronunciation, and writing skills. Additionally, Instagram fosters collaborative learning and engagement through interactive tools such as comments, Reels, and live sessions. However, challenges such as multitasking and cursory content engagement can hinder the development of profound language skills. Instagram's potential as an extra learning resource is highlighted in this study, along with the necessity of its methodical incorporation into teaching methods. The results promote more research on social media optimization for language learning and advance our understanding of digital-based learning.